Accelerated terrestrial ecosystem carbon turnover and its drivers. (7th July 2020) - Wu, Donghai; Piao, Shilong; Zhu, Dan; Wang, Xuhui; Ciais, Philippe; Bastos, Ana; Xu, Xiangtao; Xu, Wenfang
Abstract: The terrestrial carbon cycle has been strongly influenced by human‐induced CO2 increase, climate change, and land use change since the industrial revolution. These changes alter the carbon balance of ecosystems through changes in vegetation productivity and ecosystem carbon turnover time ( τ eco ). Even though numerous studies have drawn an increasingly clear picture of global vegetation productivity changes, global changes in τ eco are still unknown. In this study, we analyzed the changes of τ eco between the 1860s and the 2000s and their drivers, based on theory of dynamic carbon cycle in non‐steady state and process‐based ecosystem model. Results indicate that τ eco has been reduced (i.e., carbon turnover has accelerated) by 13.5% from the 1860s (74 years) to the 2000s (64 years), with reductions of 1 year of carbon residence times in vegetation ( r veg ) and of 9 years in soil ( r soil ). Additionally, the acceleration of τ eco was examined at biome scale and grid scale. Among different driving processes, land use change and climate change were found to be the major drivers of turnover acceleration. These findings imply that carbon fixed by plant photosynthesis is being lost from ecosystems to the atmosphere more quickly over time, with important implications for the climate‐carbon cycle feedbacks. Abstract : Ecosystem carbon turnover time has been reduced by 13.5% from the 1860s (74 years) to the 2000s (64 years), implying that carbon fixed by plant photosynthesis is being lost from ecosystems to the atmosphere more quickly over time. The total reduction of 10 years in ecosystem carbon turnover time can be attributed to the reduction in vegetation carbon residence time by 1 year, and to the reduction in soil carbon residence time by 9 years. Land use change and climate change were the major factors driving the acceleration of ecosystem carbon turnover rate.